1999
DOI: 10.1017/s0007114599000690
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated thymus involution in magnesium-deficient rats is related to enhanced apoptosis and sensitivity to oxidative stress

Abstract: Experimental Mg deficiency leads to alterations in the immune response. Reduction of thymus weight and histological changes were previously observed in Mg-deficient rats after several weeks on a deficient diet, suggesting that functions of this immune organ may be affected by Mg deficiency. More recently, changes in the immune system during early Mg deficiency were shown. Thus, in the present study we examined modifications in the thymus during the early stages of Mg deficiency in weanling rats. From our resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 22 publications
3
43
0
1
Order By: Relevance
“…Magnesium plays an essential role in a wide range of fundamental cellular reactions and is considered a 'natural calcium antagonist' [28]. Evidence showing that magnesium deficiency promotes inflammation and increases sensitivity to oxidative stress has been accumulating [28,29]. Atherosclerosis is considered an inflammatory disease and the anti-inflammatory effect of Mg might provide an alternative explanation [28].…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium plays an essential role in a wide range of fundamental cellular reactions and is considered a 'natural calcium antagonist' [28]. Evidence showing that magnesium deficiency promotes inflammation and increases sensitivity to oxidative stress has been accumulating [28,29]. Atherosclerosis is considered an inflammatory disease and the anti-inflammatory effect of Mg might provide an alternative explanation [28].…”
Section: Discussionmentioning
confidence: 99%
“…To this end, mice were kept under a restricted diet: free access to food and water was allowed for only 2 h per day for 7 days. This regimen has previously been shown to increase the intracellular level of ROS [39] and to induce thymocyte apoptosis [48,49]. We therefore compared C57BL/6 and PrP -/-mice in their ability to response to this type of stress by evaluating, each day, the thymus cellularity and the distribution of thymocyte populations.…”
Section: Measurement Of the Intracellular Redox Steady State Of T Lymmentioning
confidence: 99%
“…Magnesium ions are a required cofactor in mitochondrial electron transport chain complex subunits, methylenetetrahydrofolate dehydrogenase 2, and pyruvate dehydrogenase phosphatase (Bogucka and Wojtczak, 1976;Lawson et al, 1993;Yang and MacKenzie, 1993;Soulimane and Buse, 1995). Studies on magnesium deficient cultured human cells and animals show evidence of decreased antioxidant defenses Freedman et al, 1992;Malpuech-Brugere et al, 1999), which may result from mitochondrial dysfunction though the mechanism has yet to be elucidated. However, one study has shown mitochondrial swelling and altered ultrastructure in muscle taken from magnesium-deficient animals (Rock et al, 1995).…”
Section: Metals Necessary For Mitochondria Not Used Directly In the Hmentioning
confidence: 99%